PENERAPAN SISTEM PEMBUKTIAN OLEH HAKIM DALAM PROSES PEMERIKSAAN PERKARA TINDAK PIDANA PENCUCIAN UANG - Yona Lamerossa Ketaren; Bismar Nasution; Mahmud Mulyadi; Madiasa Ablisar (Universitas Sumatera Utara, 2018)
ABSTRACT The proceedings of money laundering actors initially place the proceeds of crime into a financial service provider such as a bank, then transfer between different accounts, and spend money on proceeds of crime to purchase goods. The most important principles in the proof of money laundering crime are the presumption of innocence to prove the defendant's crime and reverse proof. The application of a reversed verification system for criminal acts of money laundering in court is not applied independently to blame the defendant or his assets / assets involved in money laundering. The money laundering law still requires sufficient evidences to be required, which means that a minimum of two valid evidences are required. The obligation of the accused to prove that pursuant to Article 77 of the Money Laundering Law related to the element of